How Success Versus Failure Cases Support Knowledge Construction in Collaborative Problem-Solving. (October 2019) - Tawfik, Andrew A.; Kim, Kyung; Hogan, Maureen; Msilu, Fortunata
Theorists suggest that collaboration is a key aspect in online, inquiry-based learning. However, research finds that meaningful interaction is challenging, and learners struggle to sustain interaction. One way to scaffold collaborative problem-solving is through case libraries; however, few studies have explored how the type of experience depicted in a case library (success and failure) catalyzes learning. To address this gap, this study explored how the presence of success versus failure case libraries supports learning in terms of understanding of the problem space, conceptual space, knowledge construction convergence, and social network interaction. Results found no differences between conditions when discussing the problem space. However, results found that the failure group outperformed the success condition in terms of conceptual space, knowledge construction convergence, and social network interaction. As it relates to scaffolding using case-based reasoning theory and failure-driven memory theory, the failure cases helped to scaffold learners understanding of the broader conceptual space, knowledge construction, and learner–learner interaction. Additional implications for inquiry-based learning and scaffolding using case-based reasoning theory and failure-driven memory theory are provided.